Generic Adaptively Secure Searchable Phrase Encryption - Kissel Zachary A. (Proceedings on Privacy Enhancing Technologies, 2017)
In recent years searchable symmetric encryption has seen a rapid increase in query expressiveness including keyword, phrase, Boolean, and fuzzy queries. With this expressiveness came increasingly complex constructions. Having these facts in mind, we present an efficient and generic searchable symmetric encryption construction for phrase queries. Our construction is straightforward to implement, and is proven secure under adaptively chosen query attacks (CQA2) in the random oracle model with an honest-but-curious adversary. To our knowledge, this is the first encrypted phrase search system that achieves CQA2 security. Moreover, we demonstrate that our document collection preprocessing algorithm allows us to extend a dynamic SSE construction so that it supports phrase queries. We also provide a compiler theorem which transforms any CQA2-secure SSE construction for keyword queries into a CQA2-secure SSE construction that supports phrase queries.